An exploratory study of spectators' motivation in football. (6th June 2007) - Correia, Abel; Esteves, Sandra
Football matches in Portugal attract a large number of spectators every week of the season. In this study, we investigate spectators' motivation to attend live football events, by submitting a questionnaire at a major final. An analysis regarding the latent variables, sex and age differences is undertaken. Conclusions and remarks on possible marketing strategies are suggested.